2015
DOI: 10.1038/eye.2015.110
|View full text |Cite
|
Sign up to set email alerts
|

A review of therapies for diabetic macular oedema and rationale for combination therapy

Abstract: Diabetic macular oedema (DMO) is responsible for significant visual impairment in diabetic patients. The primary cause of DMO is fluid leakage resulting from increased vascular permeability through contributory anatomical and biochemical changes. These include endothelial cell (EC) death or dysfunction, pericyte loss or dysfunction, thickened basement membrane, loss or dysfunction of glial cells, and loss/change of EC Glycocalyx. The molecular changes include increased reactive oxygen species, pro-inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 143 publications
(176 reference statements)
0
52
0
2
Order By: Relevance
“…Treatment with anti-VEGF agents or corticosteroids benefit a subset of patients with advanced retinopathy, specifically macular edema (2), but more effective treatments are needed for the early stage of the disease. Over the past two decades, numerous studies have demonstrated the neurodegenerative element of DR (3)(4)(5), but the underlying mechanisms of neurodegeneration remain to be clearly established.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with anti-VEGF agents or corticosteroids benefit a subset of patients with advanced retinopathy, specifically macular edema (2), but more effective treatments are needed for the early stage of the disease. Over the past two decades, numerous studies have demonstrated the neurodegenerative element of DR (3)(4)(5), but the underlying mechanisms of neurodegeneration remain to be clearly established.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of combining corticosteroids with anti-VEGF agents are thought to be both additive and complimentary. Corticosteroids block non-VEGF-dependent inflammatory pathways, including the arachidonic acid pathway [25]. In vivo studies have confirmed that in addition to their anti-inflammatory effects, corticosteroids also inhibit the secretion of angiogenic mediators from retinal microvascular pericytes [26].…”
Section: Discussionmentioning
confidence: 99%
“…Macular oedema is the leading cause of visual loss in diabetic retinopathy patients. 13 The intravitreal anti-VEGF injection can reduce macular interstitial fluid or oedema that, even when subclinical might cause retinal functional impairment. 14 In our study, no difference in average CSMT emerged between the groups throughout the 24-week follow-up period.…”
Section: Discussionmentioning
confidence: 99%